2004
DOI: 10.5483/bmbrep.2004.37.5.625
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Proboscipedia and Caudal Gene Homologues in a Bivalve Mollusc

Abstract: Homeobox genes encode a family of transcription factors that have essential roles in regulating the development of eukaryotes. Although they have been extensively studied in different phyla, relatively little is known about homeoboxcontaining genes and their function in molluscs. In this study, we used a polymerase chain reaction to investigate homeobox genes in the bivalve mollusc Pecten maximus. Four different homeobox sequences were identified; two were homologues of the non-Hox cluster gene caudal and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…In this study, however, we discovered Hox1, Hox2, Post1 and Post2 Hox cognates in the gastropod, L. stagnalis, and in the bivalve, P. yessoensis (Figs 1, 3). Degnan & Morse (1993) also showed Hox1 and Hox2 cognates in the gastropod, H. rufescens and Carpintero et al (2004) found a Hox2 cognate in the bivalve, Pecten maximus. In P. maximus, Canapa et al (2005) also found eleven Hox cognates including Hox1, Hox2, Post1 and Post2.…”
Section: Diversity Of Hox Genes In Molluscamentioning
confidence: 99%
“…In this study, however, we discovered Hox1, Hox2, Post1 and Post2 Hox cognates in the gastropod, L. stagnalis, and in the bivalve, P. yessoensis (Figs 1, 3). Degnan & Morse (1993) also showed Hox1 and Hox2 cognates in the gastropod, H. rufescens and Carpintero et al (2004) found a Hox2 cognate in the bivalve, Pecten maximus. In P. maximus, Canapa et al (2005) also found eleven Hox cognates including Hox1, Hox2, Post1 and Post2.…”
Section: Diversity Of Hox Genes In Molluscamentioning
confidence: 99%
“…Lys, Cys, and Asp at positions 24, 27, and 39, respectively, have helped to determine to which group Mgox3 belongs. We were unable to identify a labial ortholog in M. galloprovincialis or the scallop P. maximus (Carpintero et al, 2004) although its presence has been reported in gastropods (Degnan and Morse, 1993;Hinman et al, 2002) and the cephalopod Euprymna scolopes (Callaerts et al, 2002;Lee et al, 2003).…”
Section: Anterior Group Genesmentioning
confidence: 64%
“…Genomic DNA was extracted from the muscular mass of 10 adult mussels, according to Ausubel et al (1992). For the polymerase chain reaction, we used the previously described primer pair (Carpintero et al, 2004), which correspond to homeodomain consensus sequences: 5 -ATGCGGATCCAGACSYTGGARYTGGARAARGARTTYCWY-3 and 5 -ATGCAAGCTTCATSCKNCGRTTYTGRAACCARATYTTNAY-3 (TIB Molbiol, Germany). A sample of the DNA (200 ng) was amplified in 50 µL of total PCR mixture containing 1× PCR buffer, 2 mM MgCl 2 , 0.5 µM dNTPs (Roche Molecular Biochemicals), 1 µM of each primer, and 2 U Taq DNA Polymerase (Roche).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations